A influência da produção científica nas práticas de professores de educação física, ciências e matemática em escolas públicas municipais de Uruguaiana - RS - Coutinho, Renato Xavier (2010)
The expansion of scientific and technological process has been caused many changes in the society behavior leading to changes in school practices. In Brazil we are seen a great increase in scientific production of knowledge, in many fields, including education. Furthermore, the country's scientific production is based mainly on higher education institutions and their graduate programs through their theses, dissertations and papers. So, teachers must keep updated their pedagogical practices in relation to this new knowledge. Based on this, the aim of this study was to investigate the influence of the production of knowledge in the practices of teachers of the areas of Science, Mathematics and Physical Education in public schools of Uruguaiana, Rio Grande do Sul Brazil and to evaluate the scientific production of physical education related to the school context. We analyzed the techniques used by teachers to keep up actualized, how are they chosen the contents of the classes, if they use the academic production (theses, dissertations and papers) in the planning and execution of their practices and which are the references used in interventions in the classroom. In this research it was employed a questionnaire with 26 open and closed questions with teachers from public municipal Uruguaiana, of the disciplines of sciences, mathematics and physical education. Participated in our research 14 teacher of mathematics, 17 of sciences and 17 of physical education. Based on the teacher responses, we found that the academic production does not influence directly theirs practices and often the university contributes to the increase distance between higher education and basic education. However, teachers are mostly concerned with staying current with new knowledge. Regarding the development of disciplines, it was identified that teachers try to adapt the contents to the students reality, but there is some problems like: the lack of students interest, little family involvement in school daily, also structural and administrative problems. Furthermore, an increased demand on the teachers work is not followed by an improvement in the working conditions. Regarding the scientific production of physical education, our research was conducted exclusively in online field. We just analyzed the research groups, graduate programs Strictu Sensu and theses and dissertations of the physical education area. It was found that the regions south and southeast are the centers of knowledge production, and we also found a major expansion in groups, programs and theses from the 2000. We also identified the public institutions of higher education as the main research centers of physical education in all aspects evaluated in this study. Therefore, the scientific production related to the school needs to be reviewed in his spread and in their content so that they are adequate to reality, because the arrival of new knowledge in the school environment is crucial to improve teaching in schools.